Entrapment of Polysulfides by a Black‐Phosphorus‐Modified Separator for Lithium–Sulfur Batteries. Issue 44 (16th September 2016) - Sun, Jie; Sun, Yongming; Pasta, Mauro; Zhou, Guangmin; Li, Yuzhang; Liu, Wei; Xiong, Feng; Cui, Yi
Abstract : A bifunctional separator modified by black‐phosphorus nanoflakes is prepared to overcome the challenges associated with the polysulfide diffusion in lithium–sulfur batteries. It brings the benefits of the entrapment of various sulfur species via the strong binding energy and re‐activation of the trapped sulfur species due to its high electron conductivity as well as Li‐ion diffusivity.